Introduction of the Lung Allocation Score in Germany. Issue 6 (June 2014) - Gottlieb, J.; Greer, M.; Sommerwerck, U.; Deuse, T.; Witt, C.; Schramm, R.; Hagl, C.; Strueber, M.; Smits, J. M.
<x xml:space="preserve">Abstract</x> The aim of this study was to assess performance of the new lung allocation system in Germany based on lung allocation score (LAS). Retrospective analysis of waitlist (WL) outflow, lung transplantation (LTx) activity and 3‐month outcomes comparing 1‐year pre‐ and post‐LAS introduction on December 10, 2011 was performed. Following LAS introduction, WL registrations remained constant, while WL mortality fell by 23% (p = 0.04). Reductions in WL mortality occurred in patients with cystic fibrosis (CF; −52%), emphysema (chronic obstructive pulmonary disease [COPD]; −49%) and pulmonary hypertension (PH; −67%), but not idiopathic pulmonary fibrosis (IPF; +48%). LTx activity increased by 9% (p = 0.146). Compared to pre‐LAS, more patients with IPF (32% vs. 29%) and CF (20% vs. 18%) underwent transplantation and comparatively fewer with COPD (30% vs. 39%). Median LAS among transplant recipients was highest in PH (53) and IPF (49) and lowest in COPD (34). Transplantation under invasive respiratory support increased to 13% (in CF 28%, +85%, p = 0.017). Three‐month survival remained unchanged (pre: 96.1% and post: 94.9%, p = 0.94). Following LAS implementation in Germany, reductions in waiting list size and WL mortality were observed. Composition of transplant recipients changed, with fewer COPD and more IPF recipients. Transplantation under invasive respiratory support increased. Reductions in WL mortality were most pronounced among CF and PH patients.